2020
DOI: 10.1111/ijfs.14776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure treatment on the quality of prepared chicken breast

Abstract: The prepared chicken breast is a kind of new and nutritious food with the chicken breast as raw material and processed by vacuum rolling. The physicochemical properties and microstructure of chicken breast meat treated with high‐pressure can be improved obviously. It provides the foundation for the development of chicken breast in food processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…The color difference of cooked salted egg yolks at the proximate location was analyzed by Chroma Meter CR-400 (Konica Minolta Sensing, Inc., Tokyo, Japan), according to the operation manual and reference [16] . All measurements were recorded six times at a room temperature and the values of L*, a*, b* were obtained (or calculated) by the following Eq (5) : where L* is lightness, a* is red-green chromaticity, b* is yellow-blue chromaticity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color difference of cooked salted egg yolks at the proximate location was analyzed by Chroma Meter CR-400 (Konica Minolta Sensing, Inc., Tokyo, Japan), according to the operation manual and reference [16] . All measurements were recorded six times at a room temperature and the values of L*, a*, b* were obtained (or calculated) by the following Eq (5) : where L* is lightness, a* is red-green chromaticity, b* is yellow-blue chromaticity.…”
Section: Methodsmentioning
confidence: 99%
“…Thiobarbituric acid (TBARS), determined according to the method of Dong with some subtle modifications, was used to assess lipid oxidation of SEYs [16] . 5 g SEYs was dispersed 25 mL 7.5% trichloroacetic acid (TCA) with 0.1% ethylene diamine tetraacetic acid (EDTA) and homogenized at 10,000 rpm for 45 s. 2 mL filtrate, obtained through double-layered qualitative filter paper, was mixed with 2.0 mL thiobarbituric acid (TBA, 0.02 mol/L) and heated (water bath) at 95 ℃ for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…4 Ultra-high pressure can not only improve the quality of food, but also can extend the shelf life of prepared meat products. 19 TVB-N is an important index to judge the quality of chilled meat, which can reflect the decomposition of proteins and non-proteins in meat products under the action of microorganisms and endogenous enzymes, resulting in putrid substances. 27 Furthermore, we applied proteome analysis to investigate the deterioration of chicken breast during storage, and a number of differentially expressed proteins were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Color Color was analyzed as previously described by Dong et al 19 The chicken breast was cut into 4 cm thick chunks and visible subcutaneous fat and connective tissue was removed. The color of the chicken breast was determined using a colorimeter (ADCI-60-C, Chen Taike Instruments Co. Ltd, Beijing, China).…”
Section: Cooking Loss Ratementioning
confidence: 99%
“…High pressure processing (HPP) was affirmed to be an alternative for shucking of the shellfish and crustacean, as it is a non‐thermal, nutrition‐preservation, and energy‐saving technique (Aubourg, 2018; Dang et al., 2018; Dong et al., 2020). Our previous study also found that the HPP at 300 MPa for 20 min could be used for Chinese mitten crab shucking, which not only improved the yield of edible part (about 6.6%), maintained the fresh state of the crab meat, but also saved about 56% of energy consumption when compared to the thermal treatment (Ye et al., 2019).…”
Section: Introductionmentioning
confidence: 99%